Comparison of the use of screening tools for evaluating cognitive impairment in patients with Parkinson’s disease - Carlos Henrique Ferreira Camargo (Dementia & Neuropsychologia, 2016)
Background: Screening tests have been used for cognitive deficits in Parkinson’s disease (PD). Objective: This study compared the Montreal Cognitive Assessment (MoCA) test, the Mini-Mental State Examination (MMSE) and the clock drawing test for this purpose. Methods: A total of 50 patients with PD were selected, 41 (82%) were diagnosed with dementia by the criteria of the Movement Disorder Society. The test Scales for Outcomes in Parkinson’s Disease- Cognition (SCOPA-Cog) was used as the gold standard in comparison with the screening tests. Results: The MoCA test (AUC=0.906) had a sensitivity of 87.80% and specificity of 88.89%. When the MMSE was associated with the clock drawing test (AUC=0.936), it had a specificity of 66.67% and sensitivity of up to 97.56%. Conclusion: The study suggests that the MoCA test can be a good screening test in PD. However, MMSE associated with the clock drawing test may be more effective than the MoCA test.